Improving Quality of Life in Endometriosis with Internet-based Cognitive Behaviour Therapy: A Randomised Controlled Trial - Strobl, Elena; Schubert, Kathrin; Lohse, Johanna; Weise, Cornelia (18. International Congress of Behavioral Medicine (ICBM 2025), 2025)
Background Endometriosis is a chronic gynaecological condition affecting approximately 10% of individuals with a uterus of reproductive age. Symptoms include pain and infertility, which negatively affect health-related quality of life. Current treatments are primarily symptomatic (e.g. hormonal therapies, surgery), often associated with limited long-term efficacy and side effects. Furthermore, patients continuously wish for less invasive treatments. Cognitive behavioural therapy (CBT) has proven effective in improving health-related quality of life in various chronic illnesses but has not yet been studied in endometriosis. This study aimed to evaluate the efficacy of internet-based CBT (iCBT) for endometriosis in a randomised controlled trial. Methods A total of 164 endometriosis patients were recruited and randomly assigned to the intervention (n=83) or the waitlist (n=81) group. The iCBT training consisted of eight weekly modules covering topics such as cognitive restructuring and emotion regulation, with weekly therapist feedback. Primary outcomes included endometriosis-related quality of life (E-QoL) and pain-related disability, measured at baseline, post-intervention, and 3-month follow-up. Results Mixed-effects models revealed significant group x time interaction effects favouring the iCBT group for E-QoL (F(2, 270)=9.45, p<0.001) and pain-related impairment (F(2, 275)=5.18, p=0.006). Post-hoc analyses indicated improved E-QoL at post-treatment and follow-up (p=0.007) and reduced pain-related impairment at post-treatment (p=0.006) in the iCBT group compared to the control group. Conclusion The findings demonstrate that iCBT significantly improves E-QoL and reduces pain-related impairment in individuals with endometriosis. The developed iCBT program constitutes a promising intervention, underscoring the potential of psychotherapeutic approaches in managing endometriosi